Pengaruh Sikap, Norma Subjektif, Persepsi Teknologi, Tingkat Kepercayaan, Dan Kemudahan Terhadap Minat Nasabah Dalam Menggunakan Fasilitas Internet Banking Pada Bank Syariah (Studi Kasus Nasabah Bank Syariah Indonesia Kota Batu) - Chotimatul Hamidah; Maslichah Maslichah; M Cholid Mawardi (Universitas Islam Malang, 2022)
This study aimed to determine the effect of attitudes, subjective norms,perceptions of technology, level of trust, and ease of use on customer interest inusing internet banking facilities (Case study customer of Bank Syariah IndonesiaBatu City). This type of research is quantitative research. This study took asample of 100 respondents who are customers of Bank Syariah Indonesia in BatuCity. The analytical tool used is Multiple Linear Regression Analysis using SPSS25. The results of this study indicate that the independent variable, namelyattitude (X1) has a positive and significant effect on interest (Y), subjective norm(X2) has a negative effect on interest (Y). , the perception of technology (X3) has anegative effect on interest (Y), the level of trust (X4) has a positive and significanteffect on interest (Y), ease of use (X5) has a positive and significant effect oninterest (Y). In contrast, the variabel Attitude (X1), Subjektive Norm (X2),Perception of Technology (X3), Level of Trust (X4), and Ease of Use (X5)have apositive and significant effect simultaneously on Interest.